An Applicable Framework for Understanding Successful Aging of People Living with HIV and Comorbid Chronic Obstructive Pulmonary Disease - Byun JY; Chapman Lambert C; Fazeli PL; Goodin BR; Iyer AS; Kempf MC; Wise JM; Lee Y; Batey DS; Vance DE (Dove Medical Press, 2024)
Jun Y Byun,1 Crystal Chapman Lambert,1 Pariya L Fazeli,1 Burel R Goodin,2 Anand S Iyer,1,3 Mirjam-Colette Kempf,1 Jenni M Wise,1 Yookyong Lee,4 David Scott Batey,5 David E Vance1 1School of Nursing, University of Alabama at Birmingham, Birmingham, AL, USA; 2School of Medicine, Washington University in St. Louis, St. Louis, MO, USA; 3Division of Pulmonary, Allergy, and Critical Care Medicine, University of Alabama at Birmingham, Birmingham, AL, USA; 4Department of Social Work, College of Arts and Sciences, University of Alabama at Birmingham, Birmingham, AL, USA; 5School of Social Work, Tulane University, New Orleans, LA, USACorrespondence: Jun Y Byun, School of Nursing, University of Alabama at Birmingham, 1701 University Boulevard, Birmingham, AL, 35294-4410, USA, Tel +1 205 427 5878, Email junbyun@uab.eduAbstract: Chronic obstructive pulmonary disease (COPD) is a fatal chronic disease experienced by 10% of people living with HIV (PLWH). As the population of older PLWH continues to increase, the prevalence of COPD is anticipated to grow as well. Despite this concerning trend, there is a lack of theoretical models to guide clinical practice and research on aging with HIV and COPD. To address this gap, this article describes the Baltes and Baltes' SOC (Selective Optimization with Compensation) Model as a guiding framework for understanding successful aging of PLWH with COPD. The article highlights eight areas of aging (eg, length of life, biological health, mental health, cognitive efficiency, social competence, productivity, personal control, and life satisfaction) with HIV and with COPD and the potential synergetic effects of having two critical chronic diseases. Drawing from a synthesis of literature, we adapted the SOC model to include dedicated areas specifically tailored for HIV, COPD, and the intersectional areas impacted by both conditions. Furthermore, we integrated bidirectional relationships within the eight areas of aging into the model, aiming to enhance the practical application of the modified model. Based on the identified gaps in the literature, implications for clinical practice, research, and future theoretical developments are provided.Keywords: COPD, HIV, cognitive efficiency, length of life, successful aging